The characteristics of the tumor immune microenvironment in colorectal cancer with different MSI status and current therapeutic strategies - Qingzhe Wang; Min Yu; Shuang Zhang (Frontiers in Immunology)
Colorectal cancer (CRC) remains a significant cause of cancer-related mortality worldwide. Despite advancements in surgery, chemotherapy, and radiotherapy, the effectiveness of these conventional treatments is limited, particularly in advanced cases. Therefore, transition to novel treatment is urgently needed. Immunotherapy, especially immune checkpoint inhibitors (ICIs), has shown promise in improving outcomes for CRC patients. Notably, patients with deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) tumors often benefit from ICIs, while the majority of CRC cases, which exhibit proficient mismatch repair (pMMR) or microsatellite-stable (MSS) status, generally show resistance to this approach. It is assumed that the MSI phenotype cause some changes in the tumor microenvironment (TME), thus triggering antitumor immunity and leading to response to immunotherapy. Understanding these differences in the TME relative to MSI status is essential for developing more effective therapeutic strategies. This review provides an overview of the TME components in CRC and explores current approaches aimed at enhancing ICI efficacy in MSS CRC.